КЛИНИЧЕСКИЕ И ПРОГНОСТИЧЕСКИЕ АСПЕКТЫ МИКРОАЛЬБУМИНУРИИ У ЖИТЕЛЕЙ ГОРОДА ТВЕРИ - О. Б. Поселюгина (SINAPS LLC, 2014)
Aim of study - to evaluate prevalence of microalbuminuria and its correlation with other risk factors of cardiovascular diseases in Tver. Study was done as a part of regional program of prophylaxis of chronic renal failure. From 150 patients we analyzed: anamnesis, BMI, blood pressure. For all patients we perform test for microalbuminuria (test strips MicroAlbuphan). In 45 patients (30%) creatinine in blood and GFR (Cocraft-Goldt) were measured. Analysis of microalbuminuria allows to reveal patients with risk of cardiovascular diseases. We reveal correlation of microalbuminuria with diabetes mellitus, duration of arterial hypertension, duration of smoking, obesity, GFR. More then 1⁄2 patients demonstrate chronic renal disease of 2 stage. It is very important in case it was found at out-patient department.